Three soldiers in a dugout: the modern conflict archaeology of a burnt down Second World War underground structure on the Hanko Front - Fast Jan; Väisänen Teemu (Finland, 2025)
In 2020, Hangö Sommaruni (Hangö summer university) arranged a two-week-long conflict archaeology field school, that focused on the archaeological research of the Hanko Front. The excavations uncovered remains of a burnt dugout, which were then associated with a dugout described in a memoir by lieutenant Åke Kretz (2004). In further research, the charred remains were excavated in order to discover the cause of the fire. Among a plenty of personal items, a fallen storm lantern was found in the middle of the shelter, suggesting that an accident had led to the unfortunate events.